ORTHODOX CHRISTIANITY HOLIDAYS: HERITAGE OF SERBIAN CULTURE (Heritage, 2023)
This scientific paper deals with religious Orthodox holidays and their significance within Serbian culture. The facts that celebration of religious holidays has been very widespread in recent years and that they have been receiving extensive media coverage are indicative of their considerable social importance and topicality. Religious holidays are an inalienable part of the Serbian national heritage, and the UNESCO has even declared slavas to be part of global immaterial cultural heritage. Religious holidays have always had the mission of socializing social groups, as well as individuals. The Orthodox approach to religion has never pretended to abolish or replace before-Christian holidays and rituals with Christian ones. It merely enriched them, drawing on them and endowing them with novel, Christian raiment. This is the very reason why the Orthodox tradition is exceptionally rich in symbiotic layers of the rustic and the Christian. Many old, before-Christian holidays have been preserved thus, acquiring new functions, while the Orthodox Christianity introduced elements of the Eternal, without interfering much with the ingrained habits of community life of earlier eras.
Keywords: Religious holidays, Orthodox Christianity, Heritage, Serbian culture, Patron Saint Day.